Analysis of a surgical series of 21 cerebral radiation necroses - Campos, Benito; Neumann, Jan-Oliver; Hubert, Alexander; Adeberg, Sebastian; El-Shafie, Rami; Deimling, Andreas von; Bendszus, Martin; Debus, Jürgen; Bernhardt, Denise; Unterberg, Andreas (World neurosurgery, 2020)
Background - There is no standard approach to differentiate cerebral radiation necrosis from tumor recurrence and no standard treatment pathway for symptomatic lesions. In addition, reports on histology-proven radiation necrosis and the underlying pathophysiology are scarce and highly relevant. - Methods - Our monocentric, retrospective analysis included 21 histology-proven cerebral radiation necroses. Our study focused on 1) potential risk factors for the development of radiation necrosis, 2) radiologic and histopathologic features of individual necroses, and 3) the suitability of previously reported magnetic resonance imaging (MRI)-based methods to identify radiation necroses based on specific structural image features. - Results - Average time between radiation treatment and development of necrosis was 4.68 years (95% confidence interval, 0.19-9.55 years). Matching available MRI data sets with those of patients with tumor lesions, we compared specificity and sensitivity of 3 previously reported methods to identify radionecrosis based on imaging criteria. In our hands, none of these methods reached a sensitivity ≥70%. Radionecrosis presented with large edema and showed increased levels of cell proliferation, as inferred by Ki-67 staining. Surgical removal of radiation necrosis proved to be a safe approach with low permanent morbidity (<5%) and no mortality. - Conclusions - Although the overall incidence of cerebral radiation necrosis is low, our data suggest an increasing incidence over the last 2 decades, which is likely associated with the use of stereotactic radiotherapy. There are no imaging standards to identify radiation necrosis on standard MRI with structural sequences. Surgical removal of radiation necrosis is associated with low morbidity and mortality.